2019
DOI: 10.1002/adem.201800920
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Rolling Texture of AZ31 Mg Alloy with Calcium and Tin Addition

Abstract: A small amount of Ca and Sn is added into AZ31 alloy separately to modify its deformation behavior and optimized rolling texture. Results show that addition of Sn increases the activation of twinning in AZ31. Some unusual double twins, inducing {101¯2}‐true{10true1¯2true} and {101¯3}‐true{10true1¯2true} double twins, are activated in AZ31–0.5Sn alloy. Refined grains with similar orientation as their parents are produced by continuous static recrystallization, which limits texture modification in AZT310. Ca giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Therefore, other elements, such as calcium, are added, thereby creating thermally stable intermetallic particles with Al (Al 2 Ca) and limiting the formation of the thermally unstable Mg 17 Al 12 phase. It has previously been shown that the addition of Ca in AZ31 Mg alloy softened prismatic slips and the difference between CRSS basal and CRSS prismatic decreased considerably [34,[44][45][46][47][48][49][50]. Although Ca is relatively more cost-effective than RE elements, it is crucial to consider that both the extraction of elemental Ca and the integration of Mg-Ca master alloy can increase production costs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, other elements, such as calcium, are added, thereby creating thermally stable intermetallic particles with Al (Al 2 Ca) and limiting the formation of the thermally unstable Mg 17 Al 12 phase. It has previously been shown that the addition of Ca in AZ31 Mg alloy softened prismatic slips and the difference between CRSS basal and CRSS prismatic decreased considerably [34,[44][45][46][47][48][49][50]. Although Ca is relatively more cost-effective than RE elements, it is crucial to consider that both the extraction of elemental Ca and the integration of Mg-Ca master alloy can increase production costs.…”
Section: Introductionmentioning
confidence: 99%